Boosting Newcastle disease vaccination efficacy under field conditions by aromatic plant essential oil extracts (Veterinary Science Development, 2014)
This study was performed to evaluate the effects of commercially available aromatic plant essential oil extracts (MixOilTM) on the protection outcome achieved after a Newcastle disease (ND) vaccination. Antibody production, after a MixOil treatment administered along with a vaccination program applying a live attenuated Newcastle disease virus (NDV) vaccine, was assessed under field conditions. The antibody response was evaluated via a Hemagglutination Inhibition test and an Enzyme-Linked Immunosorbent Assay. Later, the experimental groups were challenged with two velogenic NDV strains: Herts 33 and a local virulent NDV strain. A MixOil treatment effect with a higher dose was also examined. It was observed that ND antibody titers were enhanced when the birds were placed on a MixOil immune system-boosting program during vaccination. The mortality rate decreased by at least 50% after regular MixOil immune boosting; it also decreased following larger treatment doses. Clearly, promoting a strong bird immune system through herbal supplementation would naturally be expected to create a successful vaccination outcome and healthy flocks of birds. In addition, the results suggest that, by applying a higher dose of MixOil, the treatment can exceed its immune-stimulator benefits; it resulted in controlling the mortality outcome from the experimental ND infection.